Relationship between Serum Cytokeratin-18, Control Attenuation Parameter, NAFLD Fibrosis Score, and Liver Steatosis in Nonalcoholic Fatty Liver Disease - Kosasih S.; Zhi Qin W.; Abdul Rani R.; Chai Soon N.; Azhar Shah S.; Yaakob Y.; Raja Ali R.A.; Nazefah Abdul Hamid (Hindawi Limited, 2024)
Indexed by WOS/ Scopus